Clear Cell Renal Cell Carcinoma Metastatic to the Gynecologic Tract: A Clinicopathologic Analysis of 17 Cases. (November 2018) - Fadare, Oluwole; Desouki, Mohamed M.; Gwin, Katja; Hanley, Krisztina Z.; Jarboe, Elke A.; Liang, Sharon X.; Quick, Charles M.; Rawish, Kojo R.; Roma, Andres A.; Zheng, Wenxin; Hecht, Jonathan L.; Parkash, Vinita; et al.
Abstract : Clear cell renal cell carcinomas (CCRCC) rarely metastasizes to the gynecologic tract. In this study, we analyzed a multi-institutional data set to provide insights into the clinical, morphologic, and immunophenotypic features of this phenomenon. Seventeen metastatic CCRCC involving the gynecologic tract [ovary/fallopian tube (n=9), vulva (n=2), uterine corpus (n=3), cervix (n=2), uterine serosa (n=1)] were analyzed. Mean patient age was 62 yr (range: 45–79 yr). Most cases (15/17) presented as a recurrence 6 to 72 mo postnephrectomy, 1 case was concurrently diagnosed, and 1 case (a cervical metastasis) was diagnosed prenephrectomy. In 10 cases, metastases to other locations were identified within 6 wk of the gynecologic tract lesion. The adnexa were the most common site of metastases and the mean tumor size of adnexal metastases was 3.7 cm; in only 2 of 9 cases were metastases bilateral and only 1 had external surface nodules. The morphologic and immunohistochemical features of metastatic CCRCC were compared with those of 102 müllerian clear cell carcinomas (müllerian CCC: 49 endometrial, 53 ovarian). Although CCRCC and müllerian CCC displayed extensive morphologic overlap, a higher mitotic index and a higher frequency of an alveolar pattern were seen in CCRCC, whereas diffuse hobnail cells, hyaline globules, tubulocystic pattern, or any papillary pattern were more frequently seen in müllerian CCC. CA-IX, CD10, and renal cell carcinoma antigen were more frequently expressed in CCRCC than müllerian CCC, whereas Napsin-A, CK7, and p504S showed the reverse. PAX8 and HNF1β did not significantly distinguish between the 2 groups. In summary, gynecologic tract metastases most often occur as a relapse of a previously resected CCRCC, and these relapses may occur many years postnephrectomy. Gynecologic tract metastases are often accompanied by concurrent metastases to other organs. The gross pathology of metastatic CCRCC in the ovary may potentially overlap with primary neoplasia. However, the expected morphology and immunophenotype of CCRCC are maintained in most gynecologic tract metastases. As such, although metastatic CCRCC and müllerian CCC may display significant overlap in pathologic features, several morphologic and immunophenotypic features are useful in their distinction. Abstract : Supplemental Digital Content is available in the text.